Reciprocal effects between daily situational perceptions and borderline personality symptoms in young adulthood: the role of childhood parenting experiences. Issue 14 (23rd October 2021) - Vanwoerden, Salome; Hofmans, Joeri; De Clercq, Barbara
Abstract: Background: Recent research has emphasized the importance of within-person transactions between situational perceptions and borderline symptomatology. The current study extends current evidence by evaluating a broad range of situational perceptions and their transactions with borderline symptomatology across both private and professional contexts. Additionally, it explores whether early experiences of parental harsh punishment and emotional support during childhood, two well-established etiological factors in developmental theories of borderline symptomatology, influence the effect of daily situation perception in adulthood on borderline symptom presentation. Methods: N = 131 young adults ( Mage = 20.97, s.d. age = 1.64) completed end-of-day diaries of their borderline symptoms and perceptions of the home and school or work environment for 14 days. During their mid-childhood, reports of maternal strategies of harsh punishment and emotional support were collected. Results: Findings revealed that on the same day, borderline symptoms were associated with more negative and stressful, and less positive perceptions of both the private and professional context. Additionally, borderline symptoms predicted more negative and stressful perceptions of school/work on subsequent days. Finally, while early harsh punishment predicted overall increases in daily borderline symptoms 10 years later, emotionally supportive parenting in childhood predicted decreases in borderline symptom expression in less positive and more stressful contexts. Conclusions: The current study points to the importance of managing BPD symptoms to reduce subsequent negative perceptions of the environment, and also indicates the relevance of exploring adult person-situation processes based on early parenting experiences.